The Allium cepa bioassay to evaluate landfarming soil, before and after the addition of rice hulls to accelerate organic pollutants biodegradation - Souza, T. S. [UNESP]; Hencklein, F. A. [UNESP]; Angelis, D. F. [UNESP]; Goncalves, R. A.; Fontanetti, C. S. [UNESP] (Academic Press Inc. Elsevier B.V., 2009)
Landfarming is a soil bioremediation technology practiced by oil refineries in order to reduce or eliminate hydrocarbons from petroleum sludge. The goal of the current study was to use Allium cepa bioassay to assess landfarming and landfarming with rice hulls amendment before and after hydrocarbons biodegradation assay in the laboratory. Three cytogenetic endpoints were used: mitotic and chromosome abnormalities (MCA), micronucleus (MN) and nuclear buds (NB). Landfarming presented 13.5 g/kg of total petroleum hydrocarbons (TPHs) and caused strong clastogenic and mutagenic effects (p<0.05) in A. cepa. After 108 days of biodegradation, the landfarming reached the rate of 26.30 mmol of CO(2) released, the concentration of TPHs decreased by 27% and there was significant reduction in MCA, MN and NB. Landfarming treated with rice hulls had the highest release of CO(2), 110.9 mmol, associated with a remarkable reduction in TPHs concentration, 59%, and had the highest decrease in MCA, MN and NB (p>0.05). Our findings showed that the use of rice hulls accelerated the biodegradation efficacy of landfarming and reduced their clastogenicity, indicating that supplementary treatments are important to improve the efficiency of bioremediation processes. (C) 2009 Published by Elsevier B.V.
Keywords: Petroleum sludge; Oil refinery; Bioremediation; Genotoxicity tests